HUBUNGAN RESIKO TINGGI USIA IBU HAMIL DENGAN KEJADIAN HIPERTENSI DALAM KEHAMILAN DI PUSKESMAS BATU AJI - Husaidah, Siti; Nurbaiti, Nurbaiti (Universitas Batam, 2020)
Pregnancy is the fertilization or union of sperm and ovum and is followed by bullying or implantation. One of the diseases that often threatens pregnancy is the age at risk of developing hypertension during pregnancy. 39 (66.1%) pregnant women with hypertension, and 36 (61.0%) at risk. This study aims to determine the relationship between the high risk of maternal age and the incidence of hypertension in pregnancy at the Batu Aji Health Center, Batam City in 2020. The design of this study used analytical design or cross sectional design. The sampling technique used purposive sampling. Research respondents needed in this study were 59 respondents. Chi-Square statistical test results obtained value (p value = 0.03<0.05), indicating that Ho is rejected and Ha is accepted. Conclusion: there is a significant relationship between the high risk of maternal age and the incidence of hypertension in pregnancy at the Batu Aji Health Center, Batam City in 2020. It is hoped that pregnant women must carry out pregnancy checks regularly and need counseling and apply low-fat and high-protein foods to overcome them. the occurrence of hypertension in pregnancy.